PENINGKATAN KEMAMPUAN MENULIS PUISI MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) - Eber Felora Maru'ao; Arozatulo Bawamenewi; Riana; Mastawati Ndruru (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This classroom action research aimed to improve students’ ability in writing modern poetry through the implementation of the Project Based Learning (PjBL) model in class VIII-A of UPTD SMP Negeri 1 Sirombu during the 2024/2025 academic year. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection. The research subjects were 32 students, comprising 10 boys and 22 girls. Data were collected through observation, written tests, field notes, and documentation, then analyzed quantitatively and qualitatively. The findings revealed a significant improvement in students’ writing performance. In the first cycle, the average score was 54%, with many students still categorized as “poor.” After revisions in the second cycle, the average score increased to 89%, with the majority of students reaching the “very good” category. Students also showed greater activeness and creativity in expressing ideas through poetry. The results indicate that PjBL not only enhances students’ writing skills in terms of theme, diction, and depth of meaning but also improves motivation, participation, and collaborative learning. Therefore, PjBL can be considered an effective instructional model for teaching Indonesian language and literature, particularly in developing students’ creative writing skills.